1981
DOI: 10.1007/bf01248961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-methoxytryptophan and 5-methoxytryptamine on the reproductive system of the male golden hamster

Abstract: S.c. injection of 25 microgram of methoxytryptamine (5-MT) in oil into adult male hamsters given between 4.30 and 5 p.m. (light on from 5 a.m. to 7 p.m.: 14 L/10 D) for 51 consecutive days caused involution of the testes. Similar injections of 5-MT given between 8.30 and 9.30 a.m. completely failed to cause regression of the gonads. Under the same conditions, 5-methoxytryptophan (5-MTP) did not induce gonadal atrophy, neither in the morning nor in the late afternoon. These results indicate that, like malatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Reports exist demonstrating the atrophy of the testes and the accessory sex organs with daily injection (i.p.) of melatonin [29][30][31][32]. Intra-testicular melatonin injection also significantly decreased the weight of the seminal vesicle, an androgen-dependent organ supporting our data of decreased peripheral level of testosterone.…”
Section: Discussionsupporting
confidence: 87%
“…Reports exist demonstrating the atrophy of the testes and the accessory sex organs with daily injection (i.p.) of melatonin [29][30][31][32]. Intra-testicular melatonin injection also significantly decreased the weight of the seminal vesicle, an androgen-dependent organ supporting our data of decreased peripheral level of testosterone.…”
Section: Discussionsupporting
confidence: 87%
“…However, it is interesting to note that some of the indoles found to inhibit 2-[ 125 I] iodomelatonin binding in hamster brain have previously been shown to inhibit reproduction. For example, administration of 6-chloromelatonin or 5-methoxytryptamine to male Syrian hamsters induced testicular regression (28)(29)(30). Also, injection of 6-chloromelatonin or 6,7-dichloro-2-methylmelatonin inhibited ovulation in female rats (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that administration of pineal indoles to hamsters induces marked gonadal atrophy including reduction in the size of testes, seminiferous tubules and Leydig cells, inhibition of spermatogenesis, and diminution in size and secretory activity of seminal vesicles (Pevet et al, 1981(Pevet et al, , 1982Sackman et al, 1977;Reiter et al, 1981 a, b;Rollag, 1982;Tamarkin et al, 1976;Ooi and Ng, 1989). Concomitant with this collapse of reproductive organs is a decline in pituitary and plasma concentrations of luteinizing hormone and prolactin (Recter et al, 1981 a).…”
Section: Introductionmentioning
confidence: 99%